Preliminary investigations in integrated biocontrol of Botrytis gray mold of chickpea - and S. JAYANTHI, P.K. MUKHERJEE, M.P. HAWARE (Indian Phytopathology, 2002)
Four vinclozolin-resistant isolates of Trichoderma viride were obtained by selection on a fungicide amended medium. Three of these isolates were as effective as the original wild type isolate in suppressing Botrytis gray mold disease of chickpea in the growth room under controlled environment. Integration of vinclozolin application with application of fungicide-resistant Trichoderma proved more effective in disease control with one isolate than with the other three, although this isolate was not as effective as the others when applied by itself. The mechanism of disease control by Trichoderma was investigated. The action of Trichoderma was both preventive and curative. When applied prior to pathogen application, it prevented the pathogen from invading and colonizing the plants. When applied after the pathogen application, Trichoderma restricted growth of the lesions and prevented sporulation of the pathogen by rapid saprophytic colonization of the dead tissues.